Synthesis and Antimicrobial Evaluations of Sulfur Inserted Fluoro-Benzimidazoles - Kumar Dwivedi, Parmesh; Chaturvedi, Devdutt (Asian Journal of Chemistry, 2021)
A new series of fluorinated sulfur inserted benzimidazole analogues Za-i were synthesized and characterized. The new compounds were screened for their antimicrobial and antioxidant potential. The synthesized compounds were obtained by multiple step synthesis, initiating from the synthesis of 5-(difluoromethoxy)-1H-benzimidazole-2-thiol X. The compounds Ya-i prepared by reacting differently substituted anilines with chloroacetylchloride and triethylamine in DMF. Finally, the compound X was reacted with different derivatives of 2-chloro-N-phenylacetamide resulting in formation of titled compounds Za-i. The synthesized compounds (Za-Zi) were characterized by spectral analysis viz. 1H & 13C NMR, mass spectra, elemental analysis and IR. The in vitro antimicrobial potential against Gram-positive (S. aureus and E. faecalis) and Gram-negative bacterial (E. coli and P. aeruginosa) strains as well as fungi (A. niger and C. albicans) was recorded for the obtained compounds. Some of the compounds exhibited encouraging results (in MIC) against Gram-positive and Gram-negative bacterial strains. These studies thus suggest that the designed sulfur inserted fluoro-benzimidazoles scaffold may serve as new promising template for further amplification as antimicrobial agents.